Kontribusi Keterampilan Membaca Pemahaman terhadap Keterampilan Menulis Teks Deskripsi Siswa Kelas VII SMP Negeri 47 Padang - Aisyah Noverani; Nursaid Nursaid; Afnita Afnita; Yulianti Rasyid (AHKAM, 2026)
Reading comprehension skills play an important role in supporting students’ ability to write descriptive texts because writing activities require mastery of information, vocabulary, structure, and language accuracy. This study aims to describe descriptive text reading comprehension skills, describe descriptive text writing skills, and analyze the contribution of reading comprehension skills to descriptive text writing skills among seventh-grade students at SMP Negeri 47 Padang. This study used a quantitative approach with a descriptive method and correlational design. The study population consisted of 202 seventh-grade students in the 2024/2025 academic year, while the sample consisted of 42 students selected through proportional random sampling. Data were collected through an objective test to measure reading comprehension skills and a performance test to measure descriptive text writing skills. The data were analyzed using descriptive statistics, product-moment correlation, and the coefficient of determination. The results showed that reading comprehension skills were in the Good qualification category with an average score of 77.24, whereas descriptive text writing skills were in the More Than Adequate qualification category with an average score of 68.27. Reading comprehension skills contributed 58.22% to descriptive text writing skills. Thus, strengthening reading comprehension skills is an important aspect of descriptive text writing instruction because it contributes to improving students’ ability to understand, organize, and express information in writing.